'Dark am I, yet lovely': Tracing diabolical evil and femininities in gothic fusion tribal belly dance. Issue 3 (1st December 2014) - Dearey, Melissa
While belly dance as a dance genre has been recognized for its 'ambivalence' in terms of its empowerment of women's identities and body types and essentializing of narrowly constructed femininities, it has nonetheless in the research literature generally been regarded positively in its influence on women's spiritualities, corporalities, sexualities and overall well-being. But what about its attraction and allure in its 'darker' forms, as a way of empowering women, especially older women, and enabling them to negotiate and traverse a range of difficult, deviant, damaged and/ or otherwise negative experiences? Based primarily on a participant observation of a six-week series of dance workshops held in the north of England and drawing on my other experiences as a dancer of other belly dance forms, this article references Julia Kristeva's psychoanalytic theory of horror and the monstrous feminine to explore the meanings, experiences and performances of 'darkness' in what is belly dance's darkest genre, Gothic Fusion Belly Dance (GFBD).